Analysis of the Effect of Profitability Ratio on Stock in Cigarette Companies in Indonesia Stock Exchange - Afriani Lubis (TRIGIN PUBLISHER, 2022)
This research to determine and analyze the influence of Net Profit Margin, Return On Asset, and Earning Per Share of Stock Price in ciagarette companies in Indonesian Stock Exchange. This research period starting from 2007 until 2011. The hypothesis put forward is the Net Profit Margin, Return On Asset, and Earning Per Share simultaneously and partially influenced the Stock Price in ciagarette companies in the Indonesian Stock Exchange. This research is a causal associative type of research, namely to measures causal relationships between two or more variables through hypothesis testing. The population in this study is the company's ciagarette in Indonesia Stock Exchange a total of 3 companies. This research used saturated sampling and obtained a sample of 3 companies. The data used are secondary data Methods of data analysis using descriptive analysis method and multiple linear regression analysis. F test results showed that the independent variables Net Profit Margin, Return On Asset, and Earning Per Share simultaneously influential and significant effect on Stock Price. Partial test results (Test-t) show that the Net Profit Margin, Return On Asset and Earning Per Share has a significant influence the Stock Price in ciagarette companies in Indonesian Stock Exchange.